Time-of-Day Effects on Post-Activation Potentiation Protocols: Effects of Different Tension Loads on Agility and Vertical Jump Performance in Judokas - Karakoc, Bilal; Eken, Ozger; Kurtoglu, Ahmet; Arslan, Oguzhan; Eken, Ismihan; Elkholi, Safaa M. (Mdpi, 2025)
Background and Objectives: This study aimed to investigate the effects of different tension loads in post-activation potentiation protocols on agility and vertical jump performance across different times of day in trained judokas, addressing a significant gap in understanding the interaction between diurnal variations and post-activation potentiation protocol responses in combat sports. Materials and Methods: Seventeen male judokas (age: 21.41 +/- 1.37 years) with >= 2 years of training experience participated in the study. Participants completed three different protocols: specific warm-up, the 80% post-activation potentiation protocol, and the 100% post-activation potentiation protocol, performed both in the morning (09:00-11:00) and evening (17:00-19:00) sessions. Performance was assessed using the Illinois Agility Test and countermovement jump. Protocols were randomized and counterbalanced over a 3-week period, with a minimum 48 h recovery between sessions. Statistical analysis employed repeated measures ANOVA (3 x 2) with Greenhouse-Geisser corrections. Results: Significant differences were observed in both protocols and time interactions for agility (F = 41.691, eta p(2) = 0.864, p < 0.001; F = 23.893, eta p(2) = 0.123, p < 0.001) and countermovement jump performance (F = 7.471, eta p(2) = 0.410, p = 0.002; F = 38.651, eta p(2) = 0.530, p < 0.001). The 80% post-activation potentiation protocol demonstrated superior performance outcomes compared to both specific warm-up and 100% post-activation potentiation protocols. Evening performances were generally better than morning performances for both agility and countermovement jump; however, the protocols/time interaction was not statistically significant (p > 0.05). Conclusions: The 80% post-activation potentiation protocol was most effective for enhancing both agility and vertical jump performance in judokas, with superior results observed during evening sessions. These findings provide valuable insights for optimizing warm-up strategies in judo competition, suggesting that lower-intensity post-activation potentiation protocols might be more beneficial than maximal loading, particularly during evening competitions.
Keywords: agility performance; combat sports; diurnal variation; judokas; post-activation potentiation; tension load; vertical jump